(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Background: Tridax procumbens Linn. is a medicinal plant widely used in traditional medicine for the treatment of wounds, inflammation, and gastrointestinal disorders. The plant contains several bioactive constituents, among which quercetin is an important flavonoid responsible for various pharmacological activities. Objective: The present study aimed to develop and validate a simple HPLC method for the standardization and quantification of quercetin in Tridax procumbens Linn. leaf extract and to evaluate its in-vitro acid-neutralizing capacity as an indicator of antiulcer potential. Methods: Leaves of Tridax procumbens Linn. were extracted using methanol by maceration. Preliminary phytochemical screening was performed using standard qualitative tests. HPLC method development was carried out using a C18 packed column with a mobile phase consisting of acetonitrile, 5% orthophosphoric acid, and 1% triethylamine (50:49:1, v/v/v). Detection was performed at 380 nm using a D₂ lamp. The developed method was validated according to ICH Q2(R1) guidelines for linearity, accuracy, precision, robustness, ruggedness, limit of detection (LOD), and limit of quantification (LOQ). In-vitro antiulcer activity was assessed by determining the acid-neutralizing capacity (ANC) of the extract at different concentrations. Results: Phytochemical screening confirmed the presence of flavonoids, alkaloids, tannins, glycosides, carbohydrates, and proteins in the extract. The developed HPLC method showed excellent linearity over the concentration range of 20–120 µg/ml with a correlation coefficient (R²) of 0.9981. The regression equation obtained was y = 620.08x + 2576.1. The LOD and LOQ were found to be 123.60 µg/ml and 374.53 µg/ml, respectively. Precision studies showed %RSD values below 2%, while recovery studies demonstrated accuracy within acceptable limits. The extract exhibited appreciable acid-neutralizing activity, with the highest ANC value of 86.8 mEq/g observed at 200 mg concentration. Conclusion: The developed HPLC method was found to be simple, accurate, precise, and suitable for routine standardization of quercetin in Tridax procumbens Linn. leaf extract. The significant acid-neutralizing capacity of the extract supports its traditional use and indicates its potential as a natural antiulcer agent.